08.30 Histological features of synovial membrane of overweight/obese naive rheumatoid arthritispatients: correlations between inflammatory resident cells, bmi and response to therapy. (1st March 2017) - Alivernini, Stefano; Tolusso, Barbara; Petricca, Luca; Mario, Clara Di; Gigante, Maria Rita; Bui, Laura; Sante, Gabriele Di; Benvenuto, Roberta; Fedele, Anna Laura; Ferraccioli, Gianfranco; Gremese, Elisa
Abstract : Background: Obesity is an independent risk factor for Rheumatoid Arthritis (RA) influencing disease course and treatment response. Despite animal models, little is known about synovial tissue composition of overweight/obese RA patients at disease onset. The aim of the study was to investigate the histological features of naive RA patients based on Body Mass Index (BMI) category and its association with treatment response. Materials and methods: One-hundred RA patients [(57 DMARDs naive and 43 Methotrexate (MTX) no responder] were enrolled and underwent synovial tissue biopsy. At study entry RA patients were divided based on BMI value (BMI <25kg/m 2 =normal weight, BMI >25kg/m 2 =overweight and BMI >30 kg/m 2 =obesity). Immunohistochemistry for CD68 +, CD21 +, CD20 + and CD3 + cells was performed. Each naive RA patient was treated according to the treat to target (T2T) strategy and followed for 12 months. Results: Among the whole RA cohort, there were no significant differences in terms of demographic, immunological and clinical characteristics comparing naive to treatment and MTX no responder RA patients. However, considering naive to treatment RA, patients with BMI >30 kg/m 2 showed more likely follicular synovitis (78.6%) than normal weight RA (39.1%; p=0.02). Moreover, BMI value directly correlated with synovial aggregate grade (R=0.311; p=0.02) and histological scores of CD21 + (R=0.344; p=0.01), CD20 + (R=0.295; p=0.03) and CD3 + cells (R=0.256; p=0.05) in naive RA. In particular, ACPA - overweight/obese naïve RA patents showed higher frequency of follicular synovitis compared to ACPA - normal weight naïve RA patients (p<0.05). Conversely, considering MTX no responder RA patients, there was no significant difference in terms of synovial inflammation based on different BMI categories. However, overweight/obese MTX no responder RA showed lower frequency of follicular synovitis (48.8%) compared to overweight/obese naive RA (70.6%; p<0.05). Finally, regardless to the synovial inflammatory pattern (follicular vs diffuse), naive overweight/obese RA patients showed a worse clinical response to T2T strategy compared to normal weight naive RA at 6 and 12 months follow-up respectively (p<0.05 for both). Conclusions: Overweight and obesity are risk factors associated with higher degree of histologically proven synovitis and BMI status influences response rate to T2T regimen regardless to the synovial pattern in naive RA patients.